Синтез методів поляризаційно-часової обробки сигналів в системах мобільного зв’язку наступних поколінь - Москалець, М. В.; Савченко, Р. О. (ХНУРЕ, 2024)
Algorithms similar to spatial-temporal processing can be used for polarization-temporal processing of mobile station signals. The solution to the problem of synthesis of polarization-time signal processing methods from the standpoint of optimal stochastic control is considered. Procedures for observation, status and evaluation of the vector of weighting coefficients for adaptive antenna arrays are presented. On the basis of AAR, if necessary, it is possible to implement a spatially-polarization separated reception, which will minimize losses due to multibeam.
Keywords: обробка сигналів; система мобільного зв’язку